2021
DOI: 10.3389/fgene.2021.760225
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related Key Genes in Ovarian Cancer Based on WGCNA

Abstract: Background: Ovarian cancer (OV) is a fatal gynecologic malignancy and has poor survival rate in women over the age of forty. In our study, we aimed to identify genes related to immune microenvironment regulations and explore genes associated with OV prognosis.Methods: The RNA-seq data of GDC TCGA Ovarian Cancer cohort of 376 patients was retrieved from website. Weighted gene co-expression network analysis (WGCNA) and ESTIMATE algorithm were applied to identify the key genes associated with the immune scores. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
(45 reference statements)
4
16
0
Order By: Relevance
“…Weighted gene co-expression network analysis (WGCNA) is a widely used method in screening candidate biomarkers and exploring the relationships between gene sets and external biological clinical traits ( Langfelder and Horvath, 2008 ). Multivarious research has utilized this algorithm to identify hub genes involved in the pathogenesis of OC ( Zeleznik et al, 2020 ; Chang et al, 2021 ; Quan et al, 2021 ). Another notable bioinformatics tool based on support vector regression modeling, Cell-type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT), was developed to deconvolute cell types and dissect the cellular components at the transcription level ( Newman et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) is a widely used method in screening candidate biomarkers and exploring the relationships between gene sets and external biological clinical traits ( Langfelder and Horvath, 2008 ). Multivarious research has utilized this algorithm to identify hub genes involved in the pathogenesis of OC ( Zeleznik et al, 2020 ; Chang et al, 2021 ; Quan et al, 2021 ). Another notable bioinformatics tool based on support vector regression modeling, Cell-type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT), was developed to deconvolute cell types and dissect the cellular components at the transcription level ( Newman et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…KLRK1 is a receptor expressed by NK cells and cytotoxic T lymphocytes; binds non-covalently to DAP10 signaling protein to provide co-stimulatory or activation signals to T and NK cells ( 59 , 60 ). Both FASLG and KLRC4-KLRK1 are involved in the apoptosis of NK and T cells and cytotoxicity ( 61 , 62 ). SLAMF7 homologous interactions regulate NK cell cytolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence on its role in OC was still poor, an early study suggested that it could affect the progression by regulation the ER in OC (28). KCNA3 has been identified as a key immune-related gene in ovarian cancer, and moreover, its overexpression was associated with disease stage and superior survival (29). Other key genes, including NLGN1 (30) and GALR2 (31), were identified in the cancers, but their roles in ovarian cancer, especially in platinum sensitivity were unreported before.…”
Section: Discussionmentioning
confidence: 99%